2013
DOI: 10.1002/nme.4539
|View full text |Cite
|
Sign up to set email alerts
|

Grid dispersion analysis of plane square biquadratic serendipity finite elements in transient elastodynamics

Abstract: SUMMARYThe spatial discretisation of a continuum by the FEM introduces dispersion errors to the numerical solution of stress wave propagation. Errors of phase and group velocities and the scatter of wave propagation are induced. When these propagating phenomena are modelled by the FEM, the speed of a single harmonic wave depends on its frequency. Parasitic effects do not exist in an 'ideal' unbounded continuum. With higher order finite elements, there are optical modes in the spectrum resulting in spurious osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 57 publications
(90 reference statements)
1
39
0
Order By: Relevance
“…According to several studies (see, for instance, the works of Mullen and Belytschko and Kolman et al), it is recommended to use a mesh with a uniform grid step. Thus, an aspect ratio r equal to 1 will henceforth be adopted with the additional simplification h x = h y = h .…”
Section: Reflection Error Analysis For the Two‐dimensional Anti‐planementioning
confidence: 99%
“…According to several studies (see, for instance, the works of Mullen and Belytschko and Kolman et al), it is recommended to use a mesh with a uniform grid step. Thus, an aspect ratio r equal to 1 will henceforth be adopted with the additional simplification h x = h y = h .…”
Section: Reflection Error Analysis For the Two‐dimensional Anti‐planementioning
confidence: 99%
“…By selecting x , one may identify some important special cases: x=16/760.21 corresponds to the HRZ method with the full Gauss quadrature rule and x = 1/3 to the the ‘row sum’ method; thus, this value is outside the suitable interval of x . In , it was recommended to use the lumped mass matrix of the biquadratic serendipity FEs with x = 0.23 to obtain good dispersion behavior. In the context of that paper, we called the lumped mass matrix with this mass parameter as an ‘optimal’ lumped mass matrix for the plane square biquadratic serendipity FE.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Equations of motion describing the steady‐state vibration associated with a nodal sub‐system of a typical node { m , n } are given by boldMctrueboldüch+boldKcbolduch=bold0, and matrices may be defined as boldMc=bH2ρtrueboldM̄c,2emboldKc=bEtrueboldK̄c, where b marks the thickness and trueboldM̄c and trueboldK̄c are the mass and stiffness matrices for the reference problem (for unit properties of H , E , ρ and b , and defined ν ); for details, .…”
Section: Temporal‐spatial Dispersion Analysis With Central Differencementioning
confidence: 99%
See 1 more Smart Citation
“…A survey of computational aspects of wave problems in solids can be found in reference [5]. Recent research about this topic can be found in references [6,7].…”
Section: Introductionmentioning
confidence: 99%